2005
DOI: 10.1029/2004jb003368
|View full text |Cite
|
Sign up to set email alerts
|

Fault branching and rupture directivity

Abstract: [1] Could the directivity of a complex earthquake be inferred from the ruptured fault branches it created? Typically, branches develop in forward orientation, making acute angles relative to the propagation direction. Direct backward branching of the same style as the main rupture (e.g., both right lateral) is disallowed by the stress field at the rupture front. Here we propose another mechanism of backward branching. In that mechanism, rupture stops along one fault strand, radiates stress to a neighboring str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 40 publications
(92 reference statements)
9
72
0
Order By: Relevance
“…The surface rupture of the 1992 Landers earthquake activated multiple fault branches and illustrates the complexities of a rupture path (Sowers et al, 1994). Fliss et al (2005) studied backwards branching in this event and Bhat et al (2007) considered the interaction between the main fault and finite length branches. In addition to these strike-slip studies, Kame et al (2003) addressed the presence of branched faults in thrusting regime and Templeton et al (2010) investigated branch activation during normal faulting.…”
Section: Background On Fault Branch Geometries and Dynamic Rupture Momentioning
confidence: 99%
“…The surface rupture of the 1992 Landers earthquake activated multiple fault branches and illustrates the complexities of a rupture path (Sowers et al, 1994). Fliss et al (2005) studied backwards branching in this event and Bhat et al (2007) considered the interaction between the main fault and finite length branches. In addition to these strike-slip studies, Kame et al (2003) addressed the presence of branched faults in thrusting regime and Templeton et al (2010) investigated branch activation during normal faulting.…”
Section: Background On Fault Branch Geometries and Dynamic Rupture Momentioning
confidence: 99%
“…Previous modeling studies of earthquakes and slip in geometrically complex faults include investigation of slip of wavy faults (SAUCIER et al, 1992;CHESTER and CHESTER, 2000), slip through idealized fault bends (NIELSEN and KNOPOFF, 1998), rupture propagation into fault branches (OGLESBY et al, 2003;FLISS et al, 2005), and rupture jumps across gaps (HARRIS et al, 1991;DUAN and OGLESBY, 2006;SHAW and DIETERICH, 2007). Seismicity simulations that implement region-specific models of fault systems (WARD, 1996(WARD, , 2000RUNDLE et al, 2004;ROBINSON and BENITES, 1995) have demonstrated that plausible seismicity models can be implemented that replicate basic characteristics of regional seismicity.…”
Section: Introductionmentioning
confidence: 99%
“…Peyrat et al, 2001;Aochi and Fukuyama, 2002;Fliss et al, 2005;Heinecke et al, 2014;Wollherr et al, 2018]. Together with detailed analysis of the recorded strong ground motions [e.g., Campbell and Bozorgnia, 1994], rupture transfer mechanisms [e.g., Wesnousky, 2006;Madden and Pollard , 2012;Madden et al, 2013] and potential energy release [e.g., Dreger , 1994;Wald and Heaton, 1994] a comprehensive picture of the source kinematics and macroscopic earthquake properties has been developed.…”
Section: Introductionmentioning
confidence: 99%